PENGARUH PERCEIVED PRICE TERHADAP CUSTOMER LOYALTY MELALUI PERCEIVED QUALITY DAN CUSTOMER SATISFACTION PADA PRODUK HANDPHONE BLACKBERRY DI SURABAYA - WIDAGDO, HUBERT ANDERS (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Research conducted aimed to determine the factors that influence consumer loyalty on Blackberry mobile phones in Surabaya. Variables used in this study is Perceived Price, Perceived Quality, Customer Satisfaction and Customer Loyalty.This study uses SEM (Structural Equation Modeling), sampling technique in this study using a non-probability sampling study that used samples of 200 respondents. Characteristics of the sample are people who had used Blackberry mobile phones. The results showed that the perceived price positive effect on customer satisfaction, perceived price effect on perceived quality is positive, the effect of perceived quality on customer satisfaction is positive. perceived quality positive influence on customer loyalty, customer Satisfaction positive effect on customer loyalty. Perceived price positive influence on customer satisfaction through perceived quality, price Perceived positive effect on customer loyalty through customer satisfaction, price Perceived positive effect on customer loyalty through perceived quality.